Combinatorial quorum sensing in Pseudomonas aeruginosa allows for novel cheating strategies. Issue 8 (8th August 2020) - Gurney, James; Azimi, Sheyda; Brown, Sam P.; Diggle, Stephen P.
Abstract : In the opportunistic pathogen Pseudomonas aeruginosa, quorum sensing (QS) is a social trait that is exploitable by non-cooperating cheats. Previously it has been shown that by linking QS to the production of both public and private goods, cheats can be prevented from invading populations of cooperators and this was described by Dandekar et al . (Science 2012;338:264–266) as 'a metabolic incentive to cooperate'. We hypothesized that P. aeruginosa could evolve novel cheating strategies to circumvent private goods metabolism by rewiring its combinatorial response to two QS signals (3O-C12-HSL and C4-HSL). We performed a selection experiment that cycled P. aeruginosa between public and private goods growth media and evolved an isolate that rewired its control of cooperative protease expression from a synergistic (AND-gate) response to dual-signal input to a 3O-C12-HSL-only response. We show that this isolate circumvents metabolic incentives to cooperate and acts as a combinatorial signalling cheat, with higher fitness in competition with its ancestor. Our results show three important principles: first, combinatorial QS allows for diverse social strategies to emerge; second, restrictions levied by private goods are not sufficient to explain the maintenance of cooperation in natural populations; and third, modifying combinatorial QS responses could result in important physiological outcomes in bacterial populations.